2010
DOI: 10.1124/mol.110.065755
|View full text |Cite
|
Sign up to set email alerts
|

The Tetrahydroisoquinoline Derivative SB269,652 Is an Allosteric Antagonist at Dopamine D3 and D2 Receptors

Abstract: ABSTRACT3 H]spiperone to Chinese hamster ovary-transfected D 3 receptors when radioligands were used at 0.2 and 0.5 nM, respectively. However, even at high concentrations (5 M), SB269,652 only submaximally inhibited the specific binding of these radioligands when they were employed at 10-fold higher concentrations. By analogy, although SB269,652 potently blocked D 3 receptor-mediated activation of G␣ i3 and phosphorylation of extracellular-signal-regulated kinase (ERK)1/2, when concentrations of dopamine were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 38 publications
9
72
1
Order By: Relevance
“…For the antagonist eticlopride, 17 of the 18 residues that form its binding site are identical across the D2 and D3 receptors (Shi and Javitch, 2002;Chien et al, 2010). Interestingly, SB269652 (N-[4-[2-(7-cyano-3,4-dihydro-1H-isoquinolin-2-yl) ethyl]cyclohexyl]-1H-indole-2-carboxamide) was identified as an allosteric antagonist at both the dopamine D3 and D2 receptors (Silvano et al, 2010). Recent studies have suggested that this compound acts as a bitopic ligand with Identification of Dopamine D2/D3 Receptor PAMs the indole-2-carboaxamide moiety interacting with an allosteric pocket (Lane et al, 2014) and has a close structural similarity to the compounds identified here.…”
Section: Discussionmentioning
confidence: 99%
“…For the antagonist eticlopride, 17 of the 18 residues that form its binding site are identical across the D2 and D3 receptors (Shi and Javitch, 2002;Chien et al, 2010). Interestingly, SB269652 (N-[4-[2-(7-cyano-3,4-dihydro-1H-isoquinolin-2-yl) ethyl]cyclohexyl]-1H-indole-2-carboxamide) was identified as an allosteric antagonist at both the dopamine D3 and D2 receptors (Silvano et al, 2010). Recent studies have suggested that this compound acts as a bitopic ligand with Identification of Dopamine D2/D3 Receptor PAMs the indole-2-carboaxamide moiety interacting with an allosteric pocket (Lane et al, 2014) and has a close structural similarity to the compounds identified here.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the drug-like ligand SB269,652 [1H-indole-2-carboxylic acid {4-[2-(cyano-3,4-dihydro-1H-isoquinolin-2-yl)-ethyl]-cyclohexyl}-amide], which has a tertiary amino group and was originally discovered as an antagonist (Taylor et al, 1999). Later assessment has shown that this compound behaves as a negative modulator for D2R and D3R (Silvano et al, 2010). though its allosteric binding mode is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study of the dopamine D 2 receptor has revealed that the "pure" drug-like allosteric modulator SB269652 [trans-1H-indole-2-carboxylic acid {4-[2-(cyano-3,4-dihydro-1H-isoquinolin-2-yl)-ethyl]-cyclohexyl}-amide] (Silvano et al, 2010) appears to mediate its allostery by binding to one D 2 receptor protomer to allosterically modulate the binding of dopamine at an associated protomer . What distinguishes the molecule's behavior from other prior studies of cooperativity across dimers is the specific requirement for SB269652 to engage both the orthosteric site and a secondary pocket on the first D 2 receptor protomer to transmit its allosteric effect to the second protomer (Fig.…”
Section: Advances In Gpcr Allosterymentioning
confidence: 99%